Fraudulent pesticides in West Africa: a quality assessment of glyphosate products in Mali. Issue 1 (2nd January 2021) - Haggblade, Steven; Diarra, Amadou; Jiang, Wayne; Assima, Amidou; Keita, Naman; Traore, Abdramane; Traore, Mamadou
Abstract: Pesticide markets have grown far faster than regulatory monitoring capacity in West Africa. As a result, fraudulent pesticides (unregistered and counterfeit) have become widely available. This paper focuses on glyphosate, the region's most widely used pesticide. Purchase of 100 glyphosate samples from 50 different retailers across Mali found that 45% were fraudulent. Laboratory testing revealed that fraudulent glyphosate products contained 8-10% less active ingredient than registered products. Together, variable quality and widespread underdosing raise serious risks of accelerating weed resistance. These results suggest a clear need for more aggressive monitoring of pesticide markets, product quality and resulting environmental impacts. For practical purposes, farmers can protect themselves by purchasing only products duly registered by Mali's regulator, the Comité Sahélien des Pesticides (CSP).